A new combination in Carex (Cyperaceae): Carex auceps (de Lange & Heenan) K.A.Ford et Heenan, comb. nov. - Ford, Kerry A.; Heenan, Peter B. (Phytotaxa, 2015)
A new combination in Carex (Cyperaceae): Carex auceps (de Lange & Heenan) K.A.Ford et Heenan, comb. nov.